Intravitreal Bevacizumab for Choroidal Neovascularization Secondary to Angioid Streaks: A Long-Term Follow-Up Study. Issue 1 (January 2015) - Rosina, Chiara; Romano, Mary; Cigada, Mario; de Polo, Laura; Staurenghi, Giovanni; Bottoni, Ferdinando
Purpose: To evaluate the safety and efficacy of intravitreal bevacizumab (IVB) to treat choroidal neovascularization (CNV) in patients with angioid streaks. Methods: Retrospective chart review of 16 eyes of 10 patients treated with IVB for CNV secondary to angioid streaks between November 2005 and November 2011. Intravitreal bevacizumab was performed in all patients with a pro re nata regimen. Seven eyes received an additional photodynamic therapy and 1 eye argon laser photocoagulation. The diagnosis of CNV was confirmed by fluorescein angiography (FA) and indocyanine green (ICG) angiography; central macular thickness (CMT) was evaluated by optical coherence tomography. Outcome measures included changes in best-corrected visual acuity, retinal thickness, and degree of leakage on FA and ICG angiography. Results: The median number of IVB was 2.5 (range 1-6) during a mean follow-up of 52 months (range 30-67). Risk of recurrence increased during the first 50 weeks; then it remained stable. In 6 of 16 eyes, the CNV was obliterated with a single injection. Increasing CNV reactivation corresponded with an increased number of injections. Final visual acuity was related to initial VA and not to number of injections or shorter follow-up. Previous treatments, CMT, or baseline CNV size were not related to final visual acuity. Conclusions: Intravitreal bevacizumab proved to be well-tolerated in patients with CNV secondary to angioid streaks and in our small cohort IVB was efficacious for long-term follow-up. Larger series of patients are needed to confirm the effects of this treatment.